Habits of mind model for students at Elementary School Teacher Education Study Program in Universitas Negeri Jakarta - Maratun Nafiah, Riyadi, Pinta D. Sampurna, Arita Marini, Apri Wahyudi (International Journal of Advanced Science and Technology, 2020)
The aim of this research is to propose habits of mind model for students at Elementary School Teacher Education Study Program in Universitas Negeri Jakarta. This survey study distributed the questionnaires to 100 students at Elementary School Teacher Education Study Program in Universitas Negeri Jakarta in Indonesia. The technique of analysis in this study used Structural Equation Modeling (SEM). The results of this study confirmed that habits of mind model for students at Elementary School Teacher Education Study Program in Universitas Negeri Jakarta offered was good fit for the data. The result of research indicated that student endurance, setting one’s heart, thinking flexibly, thinking about thinking, and continuous learning have significant positive correlation with student habits of mind. Student ability of enduring unpleasant situation, never giving up in all situations, and being able to solve problems have significantly positive associations with student endurance. Student thinking before acting, designing strategies to achieve goals, considering the consequences before acting, and gathering relevant information have significantly positive relationship to setting one’s heart. Student capability of being easily modified in responding to altered circumstances, open minded, and being able to change their views when obtaining additional information have significantly positive associations with student thinking flexibly. Student understanding what is known and not known, estimating comparatively, and assessing the readiness of diverse activities have significantly positive correlation with student thinking about thinking. Student looking for something new and better, trying to improve themselves, and viewing problems, situations, pressures, conflicts, and the environment as good opportunities for learning have significantly positively related to the continuous learning. The conclusion of this study is that habits of mind model presented can be applied at Elementary School Teacher Education Study Program in Universitas Negeri Jakarta.